Pendidikan Konselor Religius - Najlatun Naqiyah (AL-TAHRIR, 2011)
The presentation of religious and spiritual issues is a common occurance in counselling. Are counselors competent to address this issue? This paper will address this issue. An exploration of the ways religion coming up in counseling will be discussed along with suggestions for its practices. The discussion will pay attention on the issue of educational counselor and the preparation for counselors to meet the spiritual and religious needs of their clients. In this paper this writer brings out discussion on counseling and its relation to religion through an attempt of rereading literatures in order to provide understanding as to how religion could be understood in the light of counseling. This paper also brings into focus the personality of counselor, and anything concerned to the relation of counseling and the religiousity of client. Issues of ethic for counseling in treating a religious client will be discussed as well. Thus, the discussion of religion and educational counselor will answer the question as to where it would lead to? In the lattest discussion of this paper, this writer’s suggestion on developing a subject of counseling and guidance in any universities offering Islamic Studies and on treatment of religious clients with religious approachment will be dealt with. From this point, this writer brings about a suggestion to the university.